Dog sperm swimming parameters analysed by computer‐assisted semen analysis of motility reveal major breed differences. Issue 5 (14th March 2019) - Valverde, Anthony; Arnau, Sandra; García‐Molina, Almudena; Bompart, Daznia; Campos, Marcos; Roldán, Eduardo Raúl S.; Soler, Carles
Contents: Dogs have undergone an intensive artificial selection process ever since the beginning of their relationship with humans. As a consequence, a wide variety of well‐defined breeds exist today. Due to the enormous variation in dog phenotypes and the unlikely chance of gene exchange between them, the question arises as to whether they should still be regarded as a single species or, perhaps, they be considered as different taxa that possess different reproductive traits. The aim of this study was therefore to characterize some male reproductive traits, focusing on kinematic characteristics of dog spermatozoa from several breeds. Thirty‐seven dogs from the following breeds were used: Staffordshire Bull Terrier, Labrador Retriever, Spanish Mastiff, Valencian Rat Hunting Dog, British Bulldog and Chihuahua. Semen samples were obtained via manual stimulation and diluted to a final sperm concentration of 50 million/ml, and they were subsequently analysed by the computer assisted semen analysis (CASA‐Mot) ISAS ® v1 system. Eight kinematic parameters were evaluated automatically. All parameters showed significant different values among breeds and among individuals within each breed. The fastest sperm cells were those of Staffordshire Bull Terriers and the slowest were recorded in Chihuahuas. The intra‐male coefficient of variation (CV) was higher than the inter‐male CV for all breeds with the Staffordshire Bull Terrier showing the lowest values. When taking into consideration the cells by animal and breed, discriminant analyses showed a high capability to predict the breed. Cluster analyses showed a hierarchical classification very close to that obtained after phylogenetic studies with genome markers. In conclusion, future workers on dog spermatozoa should bear in mind major differences between breeds and realize that results cannot be extrapolated from one to another. Because sperm characteristics are associated with breed diversity, dogs may represent a good model to examine changes in reproductive parameters associated with selection processes.